Determinan Disparitas Pembangunan Wilayah Pada Koridor Ekonomi Jawa - Santoso, Edy; Sahadati, Mila; Jumiati, Aisah; Hadi Priyono, Teguh; Estiyani, Nanik; Purtomo Somaji, Rafael (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to determine the factors that influence regional development disparities in the Java economic corridor. This research data uses secondary data taken from several official government publications. The analytical method used in this study is the panel data regression estimation method. The results of the study show that the best model for estimating the determinants of regional development disparities in the Java economic corridor is the Fixed Effect Model. The results of the estimation explain that the disparity of economic development in the Java corridor is significantly influenced by the Mean Years School (RLS) variable in a negative direction, the Investment variable also affects the disparity of economic development in the Java corridor positively and significantly, while the Unemployment variable has a positive but not significant effect.